The ability of biology teacher on pedagogical content knowledge (pck) in farms vocational high school Pangalengan and his perception on stem education - H Nashrulhaq; A Widodo; W Purwianingsih (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This study aims to describe the ability of biology teacher (teaching < 2 years) on Pedagogical Content Knowledge (PCK) and his perceptions on STEM education. The method of this study was qualitative research and the participant was one biology teacher in Farms Vocational High School Pangalengan. PCK of biology teacher was measured by asking teachers to make CoRes on wastes recycling substance then followed by interview and the perceptions of STEM Education was measured by filling the questionnaires. Data were analyzed with descriptive techniques. The study showed that biology teachers raises 5 important concepts that should be taught and focused of the material, the importance of material and student engineering design process skill, assessment of ascertaining students understanding that influence his teaching but he was not more flexible in the use of teaching strategies, knowledge that was not owned by students yet, difficulties that influence the teaching, students knowledge that influence the teaching, and the way to anticipate the lack of facilities in the school. Beside that, the biology teacher also was interested in STEM Educationalthough according to him, his students’ interest in subject matter related to STEM is still considered low.